Genomic Reconstruction of Carbohydrate Utilization Capacities in Microbial-Mat Derived Consortia - Leyn, Semen A.; Maezato, Yukari; Romine, Margaret F.; Rodionov, Dmitry A. (Frontiers in Microbiology, 2017)
Two nearly identical unicyanobacterial consortia were previously isolated from benthic microbial mats that occur in a heliothermal saline lake in northern Washington State. Carbohydrates are a primary source of carbon and energy for most heterotrophic bacteria. Since CO2 is the only carbon source provided, the cyanobacterium must provide a source of carbon to the heterotrophs. Available genomic sequences for all members of the unicyanobacterial consortia provide opportunity to investigate the metabolic routes of carbon transfer between autotroph and heterotrophs. Here we applied a subsystem-based comparative genomics approach to reconstruct carbohydrate utilization pathways and identify glycohydrolytic enzymes, carbohydrate transporters and pathway-specific transcriptional regulators in 17 heterotrophic members of the unicyanobacterial consortia. The reconstructed metabolic pathways include 800 genes, near a one-fourth of which encode enzymes, transporters and regulators with newly assigned metabolic functions resulting in discovery of novel functional variants of carbohydrate utilization pathways. The in silico analysis revealed the utilization capabilities for 40 carbohydrates and their derivatives. Two Halomonas species demonstrated the largest number of sugar catabolic pathways. Trehalose, sucrose, maltose, glucose and beta-glucosides are the most commonly utilized saccharides in this community. Reconstructed regulons for global regulators HexR and CceR include central carbohydrate metabolism genes in the members of Gammaproteobacteria and Alphaproteobacteria, respectively. Genomics analyses were supplemented by experimental characterization of metabolic phenotypes in four isolates derived from the consortia. Measurements of isolate growth on the defined medium supplied with individual carbohydrates confirmed most of the predicted catabolic phenotypes. Not all consortia members use carbohydrates and only a few use complex polysaccharides suggesting a hierarchical carbon flow from cyanobacteria to each heterotroph. In summary, the genomics-based identification of carbohydrate utilization capabilities provides a basis for future experimental studies of carbon flow in unicyanobacterial consortia.